N-poly viability and conglopolistic competition in small emerging market - Raul V. Fabella (University of the Philippines, School of Economics (UPSE), 2015)
The economic catch-up of the East Asian region went hand-in-hand with the emergence and even dominance of large quasi-state or private conglomerates. Such for example were the Zaibatsus in the pre-WWII and the Keiretsus of the post-WWII Japan and the Chaebols of South Korea which enjoyed extensive state sponsorship and the Taipan-led business empires of South and South East Asia which were largely autonomic. The trend continues to this day especially in the People's Republic of China. This dominance was not just an accidental fixture but the natural result of the economic and social environments prevalent in emerging markets. After reviewing the literature on why a few large private conglomerates tended to dominate the landscape of less developed economies in a rapid catch-up mode, we attempt a game theoretic account for the spread of these firms across different markets. We first define the concept of "n-poly viability" or the number of firms that can profitably Cournot compete in a market of a given the size and fixed capital requirement. We then show that conglopolistic competition (conglomerates competing in many markets) is a subgame perfect equilibrium of an entry game among initial monopolists and that this evolution is consumer welfare-improving. We identify the conditions under which only one firm or no firm benefits from the evolution.
Keywords: C79; C72; 330; behavioral; polymorphism; Bayesian; cooperation; groups